Electrochemical Determination of Glycoalkaloids Using a Carbon Nanotubes-Phenylboronic Acid Modified Glassy Carbon Electrode - Wang, Huiying (Molecular Diversity Preservation International (MDPI), 2013)
A versatile strategy for electrochemical determination of glycoalkaloids (GAs) was developed by using a carbon nanotubes-phenylboronic acid (CNTs-PBA) modified glassy carbon electrode. PBA reacts with α-solanine and α-chaconine to form a cyclic ester, which could be utilized to detect GAs. This method allowed GA detection from 1 μM to 28 μM and the detection limit was 0.3 μM. Affinity interaction of GAs and immobilized PBA caused an essential change of the peak current. The CNT-PBA modified electrodes were sensitive for detection of GAs, and the peak current values were in quite good agreement with those measured by the sensors.